Contributions of Organizational Well-being to Increase Organizational Commitment and Work Engagement for University - Rani, Sukma; Agustiani, Hendriati; Rosmayati Ardiwinata, Maya; R. , Urip Purwono (International Journal of Psychosocial Rehabilitation, 2020)
The well-being that once was meant for individuals now has developed for the organization. It was proven that organizational well-being is important because it can improve individual performance. This system also keeps the turnover low which resulted in higher commitment and more engagement from the workers. The organization that provides an effective, reflective, and affective (ERA) environment to its employees as a form of appreciation is also giving moral support to motivate employee performance. The purpose of this study is to analyze organizational well-being contributions to organizational commitment and work engagement. The participants in this study were permanent lecturers = 60 and employees = 97 (n = 157) at private universities. The sampling technique used was convenience sampling. The results showed that organizational well-being affected affective commitment with a contribution of 50.8% (R²=0.508). Organizational well-being also has an influence on normative commitment of 26% (R²=0.260) and continuance commitment of 10.8% (R²=0.108). High organizational well-being will impact organizational commitment, contributing greatly, especially to affective commitment.